THEORETICAL FOUNDATIONS OF MUSIC EDUCATION: PHILOSOPHICAL, PEDAGOGICAL, AND METHODOLOGICAL PERSPECTIVES (International journal of artificial intelligence, 2025)
This article explores the theoretical foundations of music education by examining its philosophical, psychological, and pedagogical underpinnings, as well as its historical evolution and contemporary challenges. The research emphasizes the role of music education as a socio-cultural phenomenon that not only transmits artistic values but also fosters intellectual, emotional, and moral development. Special attention is given to the dialectical relationship between tradition and innovation in shaping music pedagogy. The study critically reviews the works of international scholars who have significantly contributed to this field and analyzes methodological approaches employed in the study of music education. The paper highlights the importance of integrating interdisciplinary perspectives and contextual methodologies to ensure the sustainability and relevance of music education in a rapidly changing globalized world.